Assigning quantum labels and improving accuracy for the ro-vibrational eigenstates of H3+ calculated using ScalIT - Sarka, János; Poirier, Bill (Frontiers in Physics, 2022)
In a recent paper [AIP Adv. 11, 045033 (2021)], we carried out exact quantum dynamical calculations and computed ro-vibrational energy levels and wave functions for the H3+ molecular ion up to the dissociation threshold (at J=46) using a recently developed potential energy surface (PES)—arguably, the most accurate to date [Mol. Phys. 117, 1663 (2019)]—together with the ScalIT suite of parallel codes. In this work, we further improve the convergence accuracy and range of our ScalIT calculations, for all J values up to J = 20, to a few 10^-5 cm-1 (or better). In addition, we perform ab initio assignment of the ro-vibrational energy levels, providing vibrational `v1,v2,|l|' and rotational `J,G,U,K' quantum labels for more than 2,000 ro-vibrational states, including every single 0<= J<=20 state up to and above the barrier to linearity at 10,000 cm-1. The main underlying motivation of our work is to provide a list of reliably labeled, spectroscopically accurate energy levels in a format that can be used in spectroscopic line lists, which are based on both experimental and theoretical levels. Such line lists are of huge importance in various astrochemical and astrophysical contexts.